An herbal cream reduces erythema of sensitive skin. (25th July 2020) - Zhang, Yuanjin; Jin, Yumei; Humbert, Philippe; Fan, Xiaoqing; Cha, Yusi; Guo, Yanni; He, Li
Abstract: Background: Sensitive skin manifests itself as a syndrome defined by the occurrence of unpleasant sensations such as stinging, burning, and pruritus. Though not life‐threatening, it can negatively impact the quality of people's lives because of symptoms and clinical signs. Although some skin care products can alleviate symptoms of sensitive skin, a product that can improve multiple abnormalities of sensitive skin are largely unavailable. Aims: To assess the efficacy of a newly developed herbal cream in reducing erythema. Methods: A randomized double‐blind and self‐controlled trial was carried out on a total of 35 volunteers. The test cream (A) was applied topically to one side of the face twice‐daily, while the control cream (B) was applied to the other side of the face. Parameters were evaluated prior to, 14, and 28 days after topical applications. Primary endpoints included changes in erythema area, erythema index (EI), and a* value. Transepidermal water loss rates (TEWL), stratum corneum (SC) hydration, and lactic acid sting test (LAST) score, as well as the L* value, served as secondary endpoints. Result: Treatments with either cream A or B markedly reduced erythema area, EI, and a* value. Significant reductions in both TEWL and L* value were also observed following topical applications of either cream A or B. Moreover, cream A decreased LAST score. Finally, the satisfaction rate of cream A was higher than that of cream B. Conclusion: The new herbal cream improves cutaneous biophysical properties in subjects with sensitive skin, especially in reducing erythema.